Islamic Values in Malay Culture - Aryanto, Didi (Jurnal Kawasan Sejarah, 2023)
Known collectively as the "Malay World", the Malays are an Austronesian ethnic/ethnic group that inhabits the Malay Peninsula, the east coast of the island of Sumatra (Bangka Belitung, Jambi, Riau, Riau Islands, South Sumatra, and North Sumatra), the southern part of Thailand, the southern coast of Burma, the island of Singapore, the coast of Borneo, and small islands located nearby. In this case the author tries to present how Islam entered and developed in the Malay land which was not immediately accepted directly, but through various kinds of adjustments so that the Islamic styles brought from Arabia could be accepted in the Malay land. The method used in this writing is a qualitative research writing method using descriptive data in the form of written or spoken language from actors and people who can be observed, in the process of data collection is carried out by collecting sources that can be used as references to writings and documents that are full of facts which result in the development of cultural acculturation from various aspects of the lives of Malay people in various layers, Islamic colours are applied to oral texts or cultural practices such as mantras, songs, offerings, and dances. Mantras and chants thus appear Islamic from the outside, despite the fact that they still retain previous beliefs.